2019
DOI: 10.1109/tie.2018.2886789
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection and Severity Identification of Ball Bearings by Online Condition Monitoring

Abstract: The paper presents a fast, accurate and simple systematic approach for online condition monitoring and severity identification of ball bearings. This approach utilizes compact 1D convolutional neural networks (CNNs) to identify, quantify, and localize bearing damage. The proposed approach is verified experimentally under several single and multiple damage scenarios. The experimental results demonstrated that the proposed approach can achieve a high level of accuracy for damage detection, localization and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…The effectiveness of a 2-D CNN was demonstrated using numerical [22] and experimental [23] models of a benchmark structure by joining the data of 14 accelerometers. As an alternative, a 1-D CNN has attracted attention in electrocardiogram (ECG) detection, engine detection [24], and voltage/current detection of electronic equipment [25]. These studies confirmed the excellent performance of a 1-D CNN in damage detection.…”
Section: Introductionmentioning
confidence: 71%
“…The effectiveness of a 2-D CNN was demonstrated using numerical [22] and experimental [23] models of a benchmark structure by joining the data of 14 accelerometers. As an alternative, a 1-D CNN has attracted attention in electrocardiogram (ECG) detection, engine detection [24], and voltage/current detection of electronic equipment [25]. These studies confirmed the excellent performance of a 1-D CNN in damage detection.…”
Section: Introductionmentioning
confidence: 71%
“…the GMM-HMMs). This improvement can be partially attributed to the unique capacity of the CNNs in characterizing complex functions 44 since the CNNs can automatically integrate different levels (from low to high) of features in an end-to-end classification architecture. Moreover, the combination of CNN and MFCC has demonstrated its superiority in speech recognition and other applications of pattern recognition.…”
Section: Mfcc Feature Classification Using Cnn-based Methodsmentioning
confidence: 99%
“…In a relatively short time, 1D CNNs have become popular with a stateof-the-art performance in various signal processing applications such as early arrhythmia detection in electrocardiogram (ECG) beats [47][48][49], structural health monitoring and structural damage detection [50][51][52][53][54], high power engine fault monitoring [55] and real-time monitoring of high-power circuitry [56]. Furthermore, two recent studies have utilized 1D CNNs for damage detection in bearings [57][58][59][60]. However, in the latter study conducted by Zhang et al [60], both single and ensemble of deep 1D CNN(s) were created to detect, localize, and quantify bearing faults.…”
Section: Introductionmentioning
confidence: 99%